Subcutaneous methotrexate in patients with moderate‐to‐severe psoriasis: a critical appraisal1. (9th May 2018) - Tsakok, T.; Jabbar‐Lopez, Z.K.; Smith, C.H.
Summary: Aim: Warren et al .1 set out to assess the effect of an intensified dosing schedule of subcutaneous methotrexate in patients with moderate‐to‐severe chronic plaque psoriasis. Setting and design: This was a prospective, double‐blind, randomized (3 : 1), placebo‐controlled study, conducted across 16 centres in Germany, France, the Netherlands and the U.K. Study exposure: Methotrexate‐naive adults with a diagnosis of moderate‐to‐severe chronic plaque psoriasis for at least 6 months before baseline were randomly assigned to receive weekly subcutaneous injections of either methotrexate at a starting dose of 17·5 mg, or placebo for 16 weeks (first phase). Dose escalation to 22·5 mg per week was implemented after 8 weeks if patients did not achieve ≥ 50% improvement in Psoriasis Area and Severity Index (PASI 50). Treatment was combined with folic acid 5 mg per week. The first phase of the study was followed by an open‐label period from 16 to 52 weeks (second phase), in which both groups received weekly methotrexate injections. At week 24, dose escalation to 22·5 mg per week was possible in patients not achieving PASI 50. Outcomes: Psoriasis severity was measured using PASI. The authors also used two other psoriasis severity measures and two quality‐of‐life measures, looked at safety indices and performed a substudy analysing paired skin biopsies at baseline and week 16 (histopathology, immunohistochemistry and expression of interleukin‐17A, interferon‐γ and tumour necrosis factor‐α). Primary outcome measures: The primary outcome was the proportion of patients reaching PASI 75 at week 16. Results: In total 120 patients were included in this trial, most of whom were middle‐aged white men with long‐standing psoriasis, and the mean body mass index was 30·1 kg m −2 . PASI 75 was achieved in 41% of patients receiving methotrexate vs. 10% of patients receiving placebo (relative risk 3·93, 95% confidence interval 1·31–11·81; P = 0·0026) at week 16. Subcutaneous methotrexate was generally well tolerated, with no serious adverse events related to this treatment over the 52‐week study. Conclusion: Warren et al . conclude that the 52‐week risk–benefit profile of subcutaneous methotrexate is favourable in patients with psoriasis. Abstract : Plain language summary available online